"Not even past" : race, historical trauma, and subjectivity in Faulkner, Larsen, and Van Vechten - Stringer, Dorothy, 1976- (Fordham University Press, 2010)
Anticipating contemporary trauma studies by decades, these disparate modernists' works parallel psychoanalytic thinkers of the same era and offer important resources for psychoanalytic approaches to racial difference today.